Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages 2 Fact No. 7. — Of the twelve million families in Britain eight million have as their total savings — as their total guard, that is, against future disasters — less than £100. Half of that eight million have less than £2. The entire property of most of this bottom four million consists merely of what they stand up in and of a few sticks of furniture. Fact No. 8. — Although because of a substantial rise in the total national wealth the standard of living of what are known as the working classes has risen considerably over the past hundred years, the share of the total national wealth going to wage earners has actually fallen, not risen, during the past three-quarters of a century. It had fallen from 55 per cent. in 1860 to 40 per cent. just before the war. Inequality had increased, not decreased. This pamphlet will examine in more detail the facts of poverty ; first, the inequality of earnings which reflects that of property distribution ; then the constant companions of poverty — bad education, bad food, bad health, bad housing. Finally it will consider the inadequate measures of relief — the palliatives with which a capitalist society staves off the inevitable day when the abolition of property will clear the way for the abolition of poverty. I. INCOMES BELOW THE MINIMUM. (I) The Extent of Poverty. An estimate of the minimum requirements exclusive of rent, for a man, wife and two children, is given in the Beveridge Report. It is as follows :— £ s. d. Food. 1 6 0 Clothing 0 4 10 Fuel, Light and Household Sundries 0 4 6 Total £1 15 4 It will be seen that the last item is a very meagre allowance indeed. Entertainments and luxuries such as tobacco are not allowed for at all. Adding in 9/- which is an average working class rent, we have a total of 43s. 4d. This is according to 1938 prices; since then the cost of living has risen by 29 per cent. and therefore for the same standard of subsistence, a sum of 56s. would be necessary to-day. Mr Seebohm Rowntree, in Poverty and Progress, his social survey of York in 1936, took as the poverty line an income of 43s. 6d., after paying rent, for a man, wife and three dependent children (or the equivalent in the case of differently constituted families. This 43s. 6d. he regarded as the minimum amount for which the bare necessities of a healthy life could be secured, the figure being made up as follows:- 15X/2/98/13